Reasons for ceiling ratings in real-life evaluations of hearing aids: the relationship between SNR and hearing aid ratings - Schinkel-Bielefeld, Nadja; Ritslev, Jana; Lelic, Dina (Frontiers in Digital Health, 2023)
Introduction In past Ecological Momentary Assessment (EMA) studies, hearing aid outcome ratings have often been close to ceiling. Methods To analyze the underlying reasons for the very positive ratings, we conducted a study with 17 experienced hearing aid wearers who were fitted with study hearing aids. The acceptable noise level and the noise level where participants were unable to follow speech were measured. The participants then rated hearing aid satisfaction, speech understanding and listening effort for pre-defined SNRs between −10 and +20 dB SPL in the laboratory. These ratings were compared to ratings of a two-week EMA trial. Additionally, estimates of SNRs were collected from hearing aids during the EMA trial and we assessed whether the participants experienced those SNRs rated poorly in the laboratory in real life. Results The results showed that for hearing aid satisfaction and speech understanding, the full rating scale was used in the laboratory, while the ratings in real life were strongly skewed towards the positive end of the scale. In the laboratory, SNRs where participants indicated they could not follow the narrator (“unable to follow” noise level) were rated clearly better than the lowest possible ratings. This indicates that very negative ratings may not be applicable in real-life testing. The lower part of the distribution of real-life SNR estimates was related to participants’ individual “unable to follow” noise levels and the SNRs which were rated poorly in the laboratory made up less than 10% of the speech situations experienced in real life. Discussion This indicates that people do not seem to frequently experience listening situations at SNRs where they are dissatisfied with their hearing aids and this could be the reason for the overly positive hearing aid outcome ratings in EMA studies. It remains unclear to what extent the scarcity of such situations is due lack of encounters or intentional avoidance.